The House : An Episode in the Lives of Reuben Baker, Astronomer, and of His Wife, Alice - Field, Eugene, 1850-1895 (Salt Lake City, UT : Project Gutenberg, 2007)
"The House" by Eugene Field is a humorous and introspective novel written in the late 19th century. The story follows Reuben Baker, an astronomer, and his wife Alice as they embark on the long-anticipated adventure of purchasing a home. The narrative combines humor and poignant reflections on the desires, dreams, and challenges faced by couples as they seek to establish a family home, revealing the universal pursuit of a place to call their own. The opening of the novel introduces the Bakerds' wistful aspirations to own a home, a dream that has matured over years of planning and hope. It portrays Reuben's initial enthusiasm for a grand cottage, only to confront the realities of their financial limitations after a disappointing inheritance from Aunt Susan. As they navigate various locations and their ideal home evolves into a more modest version, Alice's excitement and determination ultimately lead her to buy the old Schmittheimer place without consulting Reuben, showcasing her personal agency and the dynamic of their relationship. The chapters set the stage for exploring the humorous complications and heartwarming moments that come with home ownership, reflecting the bittersweet journey of domestic life. (This is an automatically generated summary.)
Release date is 2007-06-11
E-text prepared by Al Haines
Keywords: Humorous stories; Home ownership -- Fiction